Privy to both worlds : the meeting of languages in Louise Erdrich's Love medicine - Gregor, Zsófia (AMERICANA E-journal of American Studies in Hungary, 2013)
This essay was written under the guidance of Profesor Enikő Bollobás, Eötvös Loránd University, Budapest.